2023
DOI: 10.1542/peds.2022-059244
|View full text |Cite
|
Sign up to set email alerts
|

Association of Maternal BMI and Rapid Infant Weight Gain With Childhood Body Size and Composition

Abstract: OBJECTIVES: Maternal prepregnancy BMI (ppBMI) and an infant’s rapid weight gain (RWG) are each associated with increased risk for childhood obesity. We hypothesized that ppBMI and RWG interact to further raise childhood obesity risk. METHODS: Mother-infant dyads (n = 414) from the Healthy Start Study, an observational prebirth cohort, were included. RWG was defined as a weight-for-age z score increase of ≥0.67 from birth to 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 54 publications
1
4
0
Order By: Relevance
“…This is consistent with previous studies, which have demonstrated that maternal obesity affects the long-term health of offspring [13,28,29]. The interaction between maternal body mass index and rapid infant weight gain jointly exacerbate the risk of childhood obesity [30]. Moreover, maternal obesity induces metabolic dysfunction in offspring, and the mechanisms involved decreased expression of genes that were related to adipocyte proliferation and differentiation, and insulin signaling and lipid mobilization [31,32].…”
Section: Discussionsupporting
confidence: 91%
“…This is consistent with previous studies, which have demonstrated that maternal obesity affects the long-term health of offspring [13,28,29]. The interaction between maternal body mass index and rapid infant weight gain jointly exacerbate the risk of childhood obesity [30]. Moreover, maternal obesity induces metabolic dysfunction in offspring, and the mechanisms involved decreased expression of genes that were related to adipocyte proliferation and differentiation, and insulin signaling and lipid mobilization [31,32].…”
Section: Discussionsupporting
confidence: 91%
“…This work has several strengths. Our sample was exclusively infants born to low-income Latinas with obesity, a demographic overlooked in GM research with a higher risk for excessive gestational weight gain and RWG of their offspring [ 30 , 31 ]. Additionally, our data collection method allowed us to connect feeding and sleep behaviors in infancy with GM composition at three years of age.…”
Section: Discussionmentioning
confidence: 99%
“…Pregnant Latina women with low-income and obesity ( n = 126) were recruited from the Special Supplemental Nutrition Program for Women, Infants, and Children (WIC) programs in Houston, TX, USA. Latina women are recognized as a particularly vulnerable group due to their increased risk of obesity, which also extends to their offspring [ 30 , 31 ]. At baseline, maternal demographics, prenatal BMI, parity, delivery mode, infant sex, and birth anthropometrics were collected via self-report.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, differences found between the cohorts may be explained by the differences in growth rates. Additionally, rapid infant weight gain can interact with maternal obesity to further increase offspring adiposity [ 59 ]. The mean prepregnancy BMI of the DOMInO sample was 26.2 kg/m 2 with an upper end of 30.5 kg/m 2 .…”
Section: Discussionmentioning
confidence: 99%